CONDITIONS FOR CREATING AN INNOVATIVE ENVIRONMENT AIMED AT DEVELOPING PROFESSIONAL AND PEDAGOGICAL CREATIVITY IN FUTURE TEACHERS - Madmarova Gulchehra Kadirovna (International Journal of Literature and Language Studies, 2026)
Abstract: Innovative educational environment is an important methodological factor in the development of professional and pedagogical creativity of future teachers, it is not just a set of technological tools, but a holistic system of pedagogical, psychological, didactic and reflexive factors that are harmoniously combined. In such an environment, the educational process moves from the traditional model focused on the transfer of knowledge to subject-subject relations that support the student's personal experience, creative activity and professional growth. This article provides information on the conditions for creating an innovative environment aimed at developing professional and pedagogical creativity in future teachers.